Time for seafood? Factors affecting land vs. sea foraging choice in breeding Mediterranean gulls - Ioannis Kalaitzakis; Federico De Pascalis; Jacopo G. Cecere; Simone Pirrello; Gabriele Meneghini; Lorenzo Serra; Diego Rubolini; Simona Imperio (Behavioral Ecology and Sociobiology, 2026)
In most bird species, breeding individuals behave as central-place foragers during reproduction, commuting regularly between the breeding site and foraging areas to find food for both self-maintenance and offspring rearing. Such movements are constrained by the need to find enough resources around the breeding site in a short time and may be modulated by several factors, including resource availability, weather, and breeding phase. By GPS-tracking 20 individuals across > 1400 foraging excursions, we characterised the foraging behaviour of Mediterranean gulls Ichthyaetus melanocephalus breeding in a coastal area, where they can forage in both terrestrial and marine habitats. Moreover, we investigated whether intrinsic factors and weather conditions affected the choice of performing foraging excursions targeting marine habitats. Females foraged closer to nesting sites than males during egg incubation compared to chick-rearing, whereas the range of male foraging excursions was unaffected by breeding stage. Overall, foraging excursions involved mostly farmland areas (43% of locations), inland waters (23%) and open sea (16%). Use of marine habitats increased from egg incubation to chick-rearing and was more frequent in males than females. Marine habitats were exploited mainly under favourable weather conditions, with small waves and moderate wind speed. Mediterranean gulls thus showed individually flexible foraging behaviour, expanding their trophic niche by increasingly relying on marine habitats late in the breeding season and possibly enhancing the provisioning of highly nutritious food to their offspring.

Adult survival has a stronger role than productivity in the annual population change of European songbirds - Inari Nousiainen; Laura Bosco; Petteri Lehikoinen; Rob Robinson; Juan Arizaga; Jaroslav Cepák; Wolfgang Fiedler; Olaf Geiter; Ian Henshaw; Christof Herrmann; Marc Illa; Henk P. van der Jeugd; et al. (Oecologia, 2025)
Biodiversity is decreasing at an alarming rate, and there is an urgent need to understand the demographic drivers behind population declines. Therefore, it is important to study the different stages of a species’ life cycle, including adult survival and productivity. It is still poorly understood whether adult survival or productivity has a stronger role in population change, and how the role of adult survival and productivity varies spatially in relation to species’ traits. We used bird ringing data from the European Constant Effort Sites (EuroCES) project from the years 2000 to 2021, with 1.2 million captures of 33 songbird species from ten European countries. We investigated the role of productivity and adult survival in annual population change and how it was affected by spatio-climatic gradient (measured as average breeding season temperature per country), migratory strategy (long- vs. short-distance and sedentary birds), and breeding habitat (forest vs. reeds) using linear mixed effect models. Overall, our results show that adult survival is a more important driver of annual population change than productivity within European songbirds. The importance of adult survival and productivity varied spatially, both having a weaker influence in warmer regions. Furthermore, the role of adult survival was stronger for long-distance migrants compared to short-distance migrants. Acknowledging that adult survival has a stronger role in annual population change than productivity can help design more robust conservation actions, especially regarding long-distance migratory songbirds.

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

Sex-mediated changes in foraging behaviour according to breeding stage in a monomorphic seabird adapted to rural habitats - Davide Scridel; Lorenzo Serra; Simone Pirrello; Marco Basso; Alessandro Franzoi; Alberto Cardillo; Chiara Mengoni; Fausto Ramazzotti; Emiliano Verza; Simona Imperio; Jacopo G. Cecere (Animal Behaviour, 2023)

Active breeding seabirds prospect alternative breeding colonies - Jelena Kralj; Aurore Ponchon; Daniel Oro; Barbara Amadesi; Juan Arizaga; Nicola Baccetti; Thierry Boulinier; Jacopo G. Cecere; Robin M. Corcoran; Anna-Marie Corman; Leonie Enners; Abram Fleishman; et al. (Oecologia, 2023)

Skin and flange colour, but not ectoparasites, predict condition and survival in starling nestlings - Simone Pirrello; Elisa Colombo; Andrea Pilastro; Matteo Pozzato; Diego Rubolini; Nicola Saino; Lorenzo Serra; Andrea Romano (Behavioral Ecology and Sociobiology, 2017)

Seasonal decline of offspring quality in the European starling Sturnus vulgaris: an immune challenge experiment - Lorenzo Serra; Simone Pirrello; Manuela Caprioli; Matteo Griggio; Alessandro Andreotti; Andrea Romano; Andrea Pilastro; Nicola Saino; Roberto Sacchi; Paolo Galeotti; Mauro Fasola; Fernando Spina; et al. (Behavioral Ecology and Sociobiology, 2012)